Comparison of the Field-Based Intermittent Running Fitness Test 30-15 and the Treadmill Multistage Incremental Test for the Assessment of Cardiorespiratory Fitness in Elite Handball Players - Mohoric, Uros; Sibila, Marko; Abazovic, Ensar; Jovanovic, Sasa; Paravlic, Armin H (International journal of environmental research and public health, 2022)
The aim of the present study was to investigate whether the physiological parameters indicative of cardiorespiratory fitness obtained during the 30-15 intermittent fitness (30-15IFT) test and the multistage laboratory treadmill endurance (TR) test differ. Nineteen elite handball players were recruited for the current study and assigned in a cross-over manner to one of two tests to be performed 48 h apart at each visit to the testing facility. The results showed that VO2max (percentage difference [PC] = 6.1%; p = 0.004) and maximal running velocity (V) (PC = 19.4%; p < 0.001) were significantly higher for the 30-15IFT test than that obtained during the TR test. Furthermore, the onset of blood lactate accumulation was shown to be significantly higher for all measures considered to predict it during 30-15IFT compared to TR as follows: VO2max (PC = 12.6%; p = 0.001), running speed (PC = 33.9%; p < 0.001), and maximal heart rate (PC = 7.5%; p < 0.001). The current study highlights the importance of sport-specific testing, particularly for measuring individual cardiorespiratory fitness in elite handball players, as TR may underestimate crucial variables used for both diagnostics and training prescription.
Keywords: Exercise Test; tělesná výkonnost; Running; srdeční frekvence; Physical Fitness; Oxygen Consumption; běh; cvičení; Exercise; Heart Rate; kardiorespirační zdatnost; spotřeba kyslíku; Cardiorespiratory Fitness; zátěžový test